Thixotropic effect of some biochemical factors in ischaemic stroke (Journal of Medical Science, 2018)
Background. Yield shear stress (YSS) well characterizes the thixotropic status of blood, that exemplifies a reversible loss of blood fluidity due to a low shear rate. At the stable haematocrit ratio YSS depends mainly on the fibrinogen level. Aim. Since the role of other biochemical factors in the YSS phenomenon in cerebral ischaemia has not been well known, we have undertaken this problem in a group of stroke patients. Material and Methods. The study was carried out in 36 patients with acute ischaemic stroke and in 12 controls. YSS was estimated by means of microviscometric method. In all subjects the concentration of the following biochemical factors were assayed: albumin, IgG, IgA, IgM, apolipoprotein A, and B, cholesterol, triglycerides, LDL, HDL and fibrinogen. Then the thixotroipic effect of all biochemical factors and their correlations to fibrinogen were estimated by means of mathematical formulas. Results. We found a positive correlation in relation to the following thixotropic effects: for all subjects and separately for patients’ group: Alb(YSS) (p < 0.001), ApoA(YSS) (p < 0.001), ApoB(YSS) (p < 0.05), chol(YSS) (p < 0.01), HDL(YSS) (p < 0.05); for patients group without additional diseases: Alb(YSS) (p < 0.05), ApoA(YSS) (p < 0.005), chol(YSS) (p < 0.05), HDL(YSS) (p < 0.02), LDL(YSS) (p < 0.05). There were not any significant correlations in controls. Conclusions. Results of the study indicated that in the interaction between the red cells and fibrinogen some additional factors appearing or activating during ischaemic process may play a role.